Dynamic fuel cell model improvement based on macroscopic energy representation - Mohamed Haidoury; Mohammed Rachidi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In this paper, a new dynamic model is presented of the proton exchange membrane fuel cell (PEMFC), using energetic macroscopic representation (EMR). This model is developed for electric automotive applications, powered by a hybrid energy storage system (HESS). The PEMFC can be used as a primary source, the supercapacitors (SC) and/or batteries are the secondary sources. The model design enables the optimization of energy use and the reduction of equipment costs, by involving the fuel cell (FC) in the transient regimes. This model takes into consideration dynamic phenomena, such as double layer capacitance, charge transfer, energy losses caused by the propagation fuel and oxidant delay. The new developed model has been tested and validated using BAHIA bench of HELION/AREVA.